2013
DOI: 10.1111/jai.12339
|View full text |Cite
|
Sign up to set email alerts
|

The effect of feeding frequency on growth performance of juvenile cobia, Rachycentron canadum (Linnaeus, 1766)

Abstract: Summary The present study was carried out to investigate the number of daily feeding sessions that results in maximum growth of juvenile cobia under laboratory conditions. Groups of eight fish (110 g) were randomly distributed in twenty 500‐L tanks and hand‐fed a commercial diet for 60 days. The same amount of feed was offered daily, divided in 1, 2, 3, four or six meals. None of the parameters associated with growth performance (survival, weight gain, specific growth rate, feed intake, condition factor or siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 38 publications
2
16
1
2
Order By: Relevance
“…An example of this practice can be observed in Moreira et al, (), where the authors did not detect significant differences in weight gain, in specific growth rate and in feed conversion for cobia Rachycentron canadumn (Linnaeus, 1766) submitted to feeding frequencies of two or three times a day. Similar results were obtained with the same species, evaluating feeding frequencies between one and six times a day within the period from 07:00 AM to 5:00 p.m. (Costa‐Bomfim et al, ). None of the parameters associated with growth performance (survival, weight gain, specific growth rate, feed intake, condition factor or size variation) showed any significant differences among treatments.…”
Section: Discussionsupporting
confidence: 76%
“…An example of this practice can be observed in Moreira et al, (), where the authors did not detect significant differences in weight gain, in specific growth rate and in feed conversion for cobia Rachycentron canadumn (Linnaeus, 1766) submitted to feeding frequencies of two or three times a day. Similar results were obtained with the same species, evaluating feeding frequencies between one and six times a day within the period from 07:00 AM to 5:00 p.m. (Costa‐Bomfim et al, ). None of the parameters associated with growth performance (survival, weight gain, specific growth rate, feed intake, condition factor or size variation) showed any significant differences among treatments.…”
Section: Discussionsupporting
confidence: 76%
“…Other authors also observed that the daily weight gain of the fish was directly proportional to the rate of feed used (Nhu et al, 2011;Al Zahrani et al, 2013;Oliveira et al, 2013). In Brazil, cobias fed with a feeding rate of 3%, at different feeding frequencies, presented a daily weight gain of 1.48 to 1.67 g (Costa-Bomfim et al, 2014). It should be noted that some authors do not adopt feeding rates, preferring the principle of apparent satiety when supplying food, which leads to great subjectivity, making it difficult to compare results.…”
Section: Resultsmentioning
confidence: 91%
“…Similar results have also been reported in Australian snapper ( Pagrus auratus ; Tucker et al., 2006), Asian seabass ( Lates calcarifer ; Biswas et al., 2010) and blunt snout bream ( Megalobrama amblycephala ; Tian et al., 2015). However, this pattern may not apply to all cultured fish, as some species show no changes in growth with increased fixed ration feeding frequency (Costa‐Bomfim et al., 2014). Our results are consistent with this pattern, as no growth performance and feed utilization efficiency improvements, nor were there any changes in the digestive enzyme activity and body composition when the number of daily feeding events increased.…”
Section: Discussionmentioning
confidence: 99%
“…The feeding frequency and ration are important factors underlying feed costs, feeding efficiency and fish growth (Silva et al., 2007). Several studies have investigated optimum feeding frequencies and rations in different fish species (Biswas et al., 2010; Cho & Bureau, 2001; Dwyer et al., 2002; Kam, Leung, & Ostrowski, 2003; Wu et al., 2019; Yuan et al., 2010), but, to our knowledge, few have combined different feeding frequencies (apparent satiety versus restricted) and rations in a single experiment (Cho et al., 2006; Costa‐Bomfim et al., 2014; Eroldogan, Kumlu, & Aktas, 2004). This is surprising because the determination of the optimum feeding regimes should include different feed management practices simultaneously.…”
Section: Introductionmentioning
confidence: 99%